O papel dos neutrófilos na imunidade inata e no desenvolvimento da resposta imune adquirida ao parasita Leishmania amazonensis - Louisa Maria de Andrade e Sousa (2009)
Neutrophils provide the first line of defense against infection and also contribute to the initiation of inflammation. However the role of neutrophils in response to Leishmania is not clear yet. Moreover, most of the studies were performed in Leishmania major model of infection, hence there is no information on the involvement of neutrophils in the immune response to Leishmania amazonensis. For this reason, the aim of this work was to investigate the role of neutrophils during the initiation of the immune response to L. amazonensis. In the present work we showed that neutrophils are the first cells to migrate to the site of infection in response to L. amazonensis, representing the predominant cellular type in the infiltrating area, and that the accumulation of these cells correlates with the production of CXCL1, CXCL2 and TNF- in the infected tissue. We compared the kinetics of neutrophil recruitment and the kinetics of chemokines and cytokines production between animals infected with L. amazonensis or L. major in order to determine if differences in the pattern of neutrophil migration would account for the failure in induction of dendritic cell activation and for the delayed expression of chemokines and cytokines observed at early stages of L. amazonensis infection. Nevertheless, we did not detect any considerable difference in neutrophil recruitment that could explain the differences observed in the immune response mounted against these parasites. Another goal was to determine the stimulus responsible for neutrophil migration to the site of infection with L. amazonensis, however the blockade of the major mediators of neutrophil recruitment was not able to prevent neutrophil migration in response to L. amazonensis, which indicates that there might be more than one stimulus acting simultaneously, or another possibility is that the parasite may produce neutrophils chemotactic factors. Furthermore, we found that the presence of neutrophils at the site of infection is essential for the formation of an intense inflammatory infiltration and for the expression of CCL2, CCL5, TNF- and IL-1 in response to L. amazonensis. Finally, we suggest that neutrophils seem to be involved in mechanisms that confer certain resistance to BALB/c mice in response to L. amazonensis, since neutrophil depletion made these animals more susceptible to infection.